Urgensi Penjatuhan Denda sebagai Sanksi Administrasi Utama: Tinjauan Kasus Persekongkolan Tender dalam Persaingan Usaha Tidak Sehat - Fionna Khantidevi Lukmadi; Ariawan Gunadi (UNES Law Review, 2023)
The present-day dynamic development of the world economy is creating enormous changes in trade. The increasing developments and needs of the global market today for adequate facilities and infrastructure for economic activities has created many forms of unhealthy competition, one of which is bid rigging which is carried out to avoid competition between business actors. This tender collusion is widespread among large business actors who want to obtain partnerships with the government in providing infrastructure. Hence, Law Number 5 of 1999 Concerning Prohibition of Monopolistic Practices and Unfair Business Competition was formulated which regulates administratif penalty due to bid rigging. Seeing that the problem of tender collusion is still occurring, this research was conducted to identify fines as the main administratif sanction to prevent collusion in tender activities. Therefore, this article was prepared with the title "The Urgency of Imposing Fines as the Main Administratif Sanction: Review of Cases of Tender Rigging in Unfair Business Competition". The object of this research is fines as administratif penalty with the aim that if fines are determined as the main administratif sanction before the main crime, healthy business competition will be created. The normative judicial with literature study is a method that will be used in this research so that we can see how fines as administratif penalty apply in cases of bid rigging.